Bridges and Borders: Entanglements of Conservation—Conservation is Development in the Forests of Nagarahole Tiger Reserve, India. (April 2021) - Gupta, Priya
The relationship between conservation and development has undergone extensive scrutiny, primarily because of they appear to be antagonistic. Recent work points instead to their complex intermingling, such as the potential economic benefits of conservation. In this article, I argue that conservation is an inherent part of the development regime. I argue this by describing conservation practices in Nagarahole Tiger Reserve that reliy on scientific governance, an essential mechanism of the development regime. I trace this regime from its inception in the colonial period through forestry operations to its continuance in the conservation regime instituted post-independence. However, despite their co-evolution, this relationship is neither simple nor straightforward. I show how everyday governance draws on customary practices and experiential knowledge of local communities inhabiting Nagarahole. This aspect is devalourized in the official governance regime to the extent that these communities are disenfranchized from their lands. By establishing conservation as development, I suggest that conservation projects should be subjected to the same level of scrutiny and examination usually allocated to development projects, which are associated with exploitation, control and drastic modification of the landscapes we inhabit.